Microbial contamination of air and protective wears in the operating theatre and surgical wards of two tertiary hospitals in Kano, Northwestern Nigeria - Nwankwo, Emmanuel Onwubiko; Nwachukwu, Ejike; Nwankwo, Patricia Onyinyechi (International Journal of Infection Control, 2015)
Bacterial airborne contamination and other fomites in the operating theatre is a major cause of nosocomial infection. This study was to evaluate the bacterial and fungal pathogens contaminating the air and protective wears in the theatre and surgical wards of two tertiary hospitals in Kano.The air sampling in the operating theatre and surgical wards were done forth nightly on 30 occasions by settle plate technique. The theatre gown was sampled by sweep plate method while samples from the face mask and hand gloves were collected by swabbing large representative areas. Isolation and identification of bacterial and fungal pathogens were carried out by standard microbiological procedure.Six bacteria genera and 2 fungi specie were observed in the theatre air while 9 bacteria genera and 2 fungi specie were observed from the ward air. Also 7 bacteria genera were observed on face mask, theatre gown and hand gloves respectively after surgery. Bacterial counts obtained by exposed plates was high after 2hrs, while an increased count was also observed 1hr after the presence of visitors in the evenings in the surgical wards.Nosocomial pathogens were identified during the research. This portends danger for surgical site infection patients.